Expectations Related to the Implementation of Performance Budget in Municipalities - Dynowska, Joanna; Cereola, Sandra Janet (Olsztyn Economic Journal, 2018)
Local governments adopt performance budgeting for a number of reasons, identified in many areas of the commune’s operations including service management, work organization, decision-making process and, above all, at every stage of the budget process. Prior research focuses mainly on the effects of performance budgeting implementation such as increased efficiency of financial resources management and increased transparency and openness of the budget and the opportunity to rationalize the costs of implementing specific tasks or improvements of the allocation of public funds. Using a questionaire, this study contributes by identifying the expectations of local governments related to the implementation of performance budgets in municipalities. A second contribution is in revealing the kinds of documents with which the performance budget should be linked and determining who should be responsible for its implementation in municipalities. The survey was conducted among 45 selected communes which are located in Warmia and Mazury voivodship. The results of the survey show that the greatest expectation in implementing the task budget was the desire to create better financial management in the municipality and to create a clearer budget for management, employees and residents of the municipality. According to the respondents, persons who should be involved in the process of budget preparation in the new task system should be the commune administrator or the treasurer of the commune. Most municipalities, as a means of transferring information about the budget assumptions, propose using a commune’s website and an information board at the commune office.